Lone Star Confederate : a gallant and good soldier of the 5th Texas Infantry - Campbell, Robert, 1844-1892 (Texas A & M University military history series ;, 2003)
Only eighteen years old when he marched off to war, young Confederate Robert Campbell already possessed the keen, perceptive eye of a seasoned journalist. After fighting with the 5th Texas Infantry Regiment in the famed Hood's Texas Brigade, Campbell recorded the first months of his service for the benefit of future generations of his family.